DIGITAL WALLET TRANSACTIONS: INSIGHT FROM ISLAMIC ECONOMIC AND LEGAL PERSPECTIVE - Munifatussaidah, Asma; Zahara, Jihan Nabila; Zein, Fuad (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: This paper aims to analyze the contemporary problems surrounding digital wallet transactions from the perspective of Islamic economic law and discuss sharia compliance in the issuance and use of digital wallets, the validity of top-up transactions, and the permissibility of benefits such as cashback within the framework of Islamic jurisprudence. Methods: This paper uses library research methods to collect, explain and analyze data related to digital wallet transactions in the context of Islamic economic law. This has been done using a normative approach and Islamic economic law, supported by descriptive analysis of the previous research, fatwas from the Indonesian Ulema Council (DSN-MUI), and related regulations from Bank Indonesia. Results: The result of this discussion is that Islamic principles allow financial transactions as long as they do not involve prohibited elements such as usury, uncertainty (gharar), maysir, and israf. Digital wallets can fulfill Islamic principles if they comply with the regulations set by Islamic law. Conclusion and suggestion: The DSN-MUI fatwa provides guidance on the use of electronic money in accordance with sharia, ensuring that digital wallet transactions are in line with Islamic legal and ethical standards. Digital wallet transactions can use various contracts, such as wadiah and qardh contracts, although there are differences of opinion among scholars regarding their validity. The compliance of digital wallets with sharia must differentiate between conventional electronic wallets and electronic wallets that comply with Sharia.